Wnt signaling inhibits casein kinase 1α activity by modulating its interaction with protein phosphatase 2A - Chen Shen; Wenhui Lu; Siva B. Merugu; Aradhana Bharti; Said M. Afify; Lauren Schnitkey; Daniel T. Wynn; Fan Yang; Thomas M. Rohwetter; Anmada Nayak; Nawat Bunnag; Carolina Cywiak; et al. (Cell Reports)
Summary: The mechanism by which Wnt signaling, an essential pathway controlling development and disease, stabilizes β-catenin has been a subject of debate over the last four decades. Casein kinase 1α (CK1α) functions as a pivotal negative regulator of this signaling pathway, initiating the events that destabilize β-catenin. However, whether and how CK1α activity is regulated in Wnt-off and Wnt-on states remains poorly understood. We now show that CK1α activity requires its association with the α catalytic subunit of protein phosphatase 2A (PPP2CA) on AXIN, the scaffold protein of the β-catenin destruction complex. Wnt stimulation induces the dissociation of PPP2CA from CK1α, resulting in CK1α autophosphorylation and its consequent inactivation. Moreover, autophosphorylated CK1α is enriched in a subset of colorectal cancers (CRCs) harboring constitutive Wnt activation. Our findings identify a mechanism by which Wnt stimulation inactivates CK1α, filling a critical gap in our understanding of Wnt signaling, with relevance for CRC.